Penanaman Karakter Peduli Lingkungan Pada Siswa Kelas V SD Negeri Pudakpayung 02 di Era New Normal - Titik Kurnia Sari; Purwadi Purwadi; Sunan Baedowi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The background of this research is how to build environmental care characters in fifth grade students of SD Negeri Pudakpayung 02 in the new normal era, and the obstacles to building environmental care characters in fifth grade students of SD Negeri Pudakpayung 02 in the new normal era. This research uses a qualitative research type. The data collection procedure was carried out using observation, interview, and documentation techniques. The results of this study are the efforts made by teachers to build environmental care characters in fifth grade students in the new normal era, namely using habituation patterns through Control Book, teaching patterns through illustrated materials and media related to the environment, and program SUSU (Sak Uwong Sak Uwit).